The elite sport classification system needs improvement, not replacement - Loland, S. (The American Journal of Bioethics, 2024)
Jennings and Braun`s (2024) article "Beyond Suppressing Testosterone: A Categorical System to Achieve a `Level Playing Field` in Sport" is a valuable contribution to the academic debate over the DSD regulations and athlete classification in sport. The authors take the World Athletics (WA) fairness justification at face value and explore its implications in practice. WA points to the need for a level playing field and, in Jennings and Braun`s interpretation, defines fairness as a situation where athletes` performance advantage over an average athlete in their category is influenced by "talent, dedication, and hard work alone" alone. Jennings and Braun demonstrate how WA`s fairness ideal has far more extensive implications than testosterone level regulation, among them the radical breakdown of binary classification into female and male categories to be replaced by a categorical system along the lines of Paralympic sport.